ANALISIS KESULITAN BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPAS KELAS IV DI SDS AL-HIDAYAH - Indrayani, Vindy; Febrianto, Priyono Tri (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This research aims to determine students' learning difficulties and describe the teacher's efforts in overcoming students' learning difficulties in science and science learning in class IV SDS Al-Hidayah. The type of research used in this research is descriptive research. The subjects of this research were the class IV homeroom teacher and 16 class IV students. The data collection techniques used were interviews, observation and documentation. To test the validity of the data, researchers used source triangulation. Based on the research results, it can be concluded that 45.54% of students experience learning disabilities in terms of delays in learning to read, spell and speak clearly in science learning. Furthermore, 68.75% of students experienced underachievement where students felt anxious when an exam was to be held. Then the last one is slow learner. Where 62.5% of students experience slow learning in terms of low learning outcomes and have awkwardness in their ability to build relationships with friends. The efforts made by the teacher in this research were the teacher becoming a facilitator and the teacher becoming a motivator in science learning.